(untitled) (International journal of artificial intelligence, 2025)
The article discusses key aspects of improving teaching methods: activating students' cognitive activity, the role of a physical experiment, developing independence and motivation, rethinking the approach to solving problems as a tool for learning, deepening intra-subject connections and transforming the role of a teacher into an organizer of the educational process. The need to adapt physics teaching to modern challenges and goals of state educational policy is substantiated. The paper also presents research methods, including the analysis of regulatory documents, scientific and pedagogical literature and advanced pedagogical experience.